Reuse of end-of-life tires and their impact on the setting time of mortars: Experimental study using a new measuring equipment. (15th June 2023) - Ferrández, Daniel; Yedra, Engerst; Recalde-Esnoz, Irantzu; del Castillo, Héctor
Abstract: End-of-Life Tires (ELT) have posed severe environmental problems for the European Union due to their slow degradation and the difficulties in recycling elastomers such as rubber. For this reason, its reincorporation into the manufacturing process of new sustainable construction materials has become an increasingly viable alternative. In this research, an experimental campaign is carried out to understand better the setting process of masonry mortars with the incorporation of ELT as a partial replacement for aggregates. To do this, a new measuring device has been developed that allows real-time monitoring of the setting process in mortars. The proprietary design equipment acquired for this research combines Arduino technology with capacitive measurement equipment. The results show how it is possible to determine in real-time the evolution of the setting of masonry mortars regardless of the type of aggregate used in its manufacture. In turn, physical and mechanical characterization of the elaborated mortars has been carried out, studying the evolution of these properties over time. It can be seen how the incorporation of ELT s reduces the mechanical resistance of the mortars but improves their dimensional stability by reducing shrinkage during setting, which is of particular interest in mortars made with recycled aggregate, specially designed for the production of prefabricated construction elements. Highlights: ELT and CDW from construction industry represent a real global environmental problem. Mortars with ELT incorporation have decreased slightly in the mixing water content. With the incorporation of ELT is observed a good dimensional stability of the mortar. The Arduino system incorporated in the developed mold allows real-time monitoring.